THE ESSENTIAL ROLE OF CONVENTIONAL RADIOGRAPHY IN COVID-19; PERSPECTIVE OF A DEVELOPING COUNTRY - Majeed, Ayesha Isani; Raza, Farheen; Riaz, Syeda Kiran; Kanwal, Jaweria (Journal of Ayub Medical College Abbottabad, 2021)
Background: The Coronavirus disease (COVID-19) pandemic has shaken the world. So far, CT has emerged as main stay of imaging whereas the local data on radiographic features of COVID-19 is sparse. Methods: Prospective study includes 402 chest X rays (CXRs) of 105 patients presenting with symptoms of COVID-19. The nature of abnormality, distribution and lung zone involvement was documented. Following British Society of Thoracic Imaging (BSTI) guidelines, CXRs were grouped into classic/ probable COVID-19, indeterminate, non-COVID-19 and normal categories. The lung involvement was scored according to modified Radiographic Assessment of Lung Edema (RALE) scoring. The follow up radiographs were assessed for disease progression and improvement. Results: Seventy-six males and 29 females with mean age of 50 years were included in our study. 47 out of 105 baseline radiographs were categorized as classic/ probable COVID-19, 26 as indeterminate, 7 as Non-Covid-19 and 25 as normal. 75 patients were positive and 30 were negative on RT-PCR testing. The sensitivity of CXR in diagnosing COVID-19 is 84%. The worsening radiographic features and higher RALE score correlates with longer hospital stay, ICU admissions and mortality. The ground glass opacities and consolidations in peripheral distribution involving bilateral mid and lower zones are the predominant findings of COVID-19 in Pakistani population. Conclusion: Combination of bilateral peripheral ground glass opacities and consolidations are the cardinal feature of COVID-19 on CXRs. The diagnostic categories described by BSTI correlates with PCR results in Pakistani population. The worsening radiographic findings correspond to poor prognosis; hence serial radiographs can be used for assessing disease course.